Foreshocks of the 2016 MS5.1 Yunlong earthquake in Western Yunnan, China, and implications for earthquake nucleationKey points - Gaohua Zhu; Hongfeng Yang; Yingying Zhang (Earthquake Science)
Monitoring the evolution of foreshocks can be a valuable way to analyze the nucleation process. Foreshocks accompanying moderate mainshocks have been recorded in the west of Yunnan Province, China. We obtain the earthquake catalog and source parameters of the 2016 Yunlong foreshocks, and discuss the implications for the nucleation processes of the earthquake in western Yunnan, China. By using the matched filter detection, we identify 343 foreshocks with a magnitude of −0.8−4.5, starting with a magnitude 1.0 foreshock approximately 3 months before the 2016 MS5.1 Yunlong mainshock. The spatial distribution of foreshocks doesn’t show localization or directional migration towards the mainshock. Coulomb stress analysis suggests a positive stress perturbation at the mainshock nucleate area. These observations indicate a cascade-triggering mechanism of the 2016 Yunlong earthquakes. We further collect published catalogs of 2021 Yangbi and 2017 Yangbi foreshocks in the adjacent area, and analyze the temporal changes in b values. The temporal changes in b values reveal precursory drops before the mainshocks.